(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper, the performance of routing protocols DSDV, OLSR and AODV using performance metrics like Packet Delivery Ratio, Average End to End delay, Packet Loss Ratio and Average Throughput within Vehicular ad hoc networks for CBR applications over UDP connection has been analyzed. Network Simulator (NS-3.19) along with mobility model generated through Simulation of Urban Mobility (SUMO) tool is used for analysis. The results are analyzed by varying node density in the network. The comparison shows that reactive protocol AODV performs better as compared to DSDV and OLSR proactive routing protocols for vehicular ad hoc networks